Crude glycerin improves feed efficiency in finishing heifers - Van Cleef, E.H.C.B.; Uwituze, S.; Alvarado, C.A.; Miller, K.A.; Van Bibber-Krueger, C.L.; Aperce, C.C.; Higgins, James J.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Crude glycerin is the principal byproduct of biodiesel production. The raw feedstocks, animal fats and vegetable oils, yield approximately 90 lb of biodiesel and 10 lb of crude glycerin for each 100 lb of input. When ingested by cattle, glycerin has two major fates: (1) direct absorption by the rumen epithelium, and (2) fermentation by microorganisms within the rumen to generate volatile fatty acid, mainly propionate. Using glycerin in feedlot cattle diets has become common, particularly as a component of liquid feed supplements. We have evaluated the use of crude glycerin in cattle diets in previous studies and generally have observed positive effects on dry matter intake and feed efficiency when fed up to 8% of the diet on a dry matter basis. Crude glycerin can be highly variable in its composition, however, containing varying proportions of residual alcohol, soaps, and salts. Our focus in the present experiment was on the sodium content of crude glycerin. We hypothesized that the high concentration of sodium in glycerin, when combined with salt that normally is incorporated into feedlot diets, would result in abnormally high levels of sodium that could have deleterious consequences for feed consumption. The objective of this study was to evaluate feedlot performance and carcass characteristics of finishing heifers fed diets containing high levels of crude glycerin in the presence and absence of added salt.
Keywords: Cattle; Crude glycerin; Feed efficiency; Heifers; Dry matter intake; Feedlot performance; Carcass characteristics